Monitoring the athlete training response: subjective self-reported measures trump commonly used objective measures: a systematic review - Saw, A. E.; Main, L. C.; Gastin, P. B. (British Journal of Sports Medicine, 2016)
Background: Monitoring athlete well-being is essential to guide training and to detect any progression towards negative health outcomes and associated poor performance. Objective (performance, physiological, biochemical) and subjective measures are all options for athlete monitoring.